Integrated Field Theoretical Evaluation of Sediment Pond Efficiency in a Tropical Mining Catchment - Cantik, Bella Koes Paulina; Sapan, Elenora Gita Alamanda; Putra, Ramon; Martin, Belly; Kevin, Josh (LIMNOTEK Perairan Darat Tropis di Indonesia, 2025)
Sediment ponds in coal mining operations serve as critical infrastructure for wastewater management. A major challenge in their operation is excessive sediment accumulation, which is often difficult to anticipate accurately, especially when relying solely on theoretical calculations. Such circumstances highlight the importance of an approach that is not solely theoretical, but also considers the actual dynamics observed in the field. The coal mining sediment pond examined in this study was initially constructed to accommodate a catchment area of 205 Ha, with a useful life of 10 years. However, the pond has reached full capacity in less than five years, 53% earlier than expected, indicating the need for re-evaluation, especially as the catchment area is planned to expand to 885 Ha. This study aims to evaluate, compare, and recalculate the sediment pond’s capacity under expanded catchment conditions (885 Ha), by integrating field-based measurements and theoretical sediment yield methods to produce a more representative design. The methods employed include the Revised Universal Soil Loss Equation (RUSLE), Lane & Kalinske’s Approach, Einstein’s Approach, Brook’s Approach, and Chang, Simons, and Richardson’s Approach. RUSLE utilizes secondary data, while the other methods incorporate both primary and secondary data. The results show a wide range of sediment transport estimates, from 20,184 m3 using Einstein’sto 507,075 m3 using Chang’s. Among the evaluated methods, Lane and Kalinske, as well as Brook, produced sediment volume estimates that closely matched field-based measurements, making them suitable for field conditions. RUSLE produced a lower-bound estimate, while Einstein and Chang’s method deviated significantly from the observed range. These findings underscore the importance of integrating field measurements with theoretical models to enhance the reliability of sediment-yield estimation and support informed decision-making in sediment pond.